Computational and Experimental Approaches in Multi-Target Pharmacology (2017)
The next frontier in pharmacology is the development of multi-target strategies in which pathological processes are controlled by pharmacologically manipulating them at many different points at once. Designing multi-target strategies will require deep understanding of the complex physiology that underlies pathological processes. It will also require the development of single drugs with multiple targets, or combinations of drugs with compatible pharmacokinetics that work synergistically to maximize desirable effects while minimizing unwanted side effects. This e-Book contains ten original articles, each addressing a different aspect of this challenge. Together they open new perspectives and show the way forward in the development of multi-target therapeutics.